Design and implementation of a health messaging protocol employed for use within a COVID-19 health dissemination platform - Colombo, Paulina M.; Freylersythe, Sarah; Sprinkle, Mary Margaret; Ernst, Kacey C.; Yubeta, Marcela; Barbati, Juliana L.; Merchant, Nirav; Iyengar, Sriram; Crane, Tracy E.; Oxnam, Maliaca; Rains, Stephen A. (Frontiers in Public Health, 2022)
Introduction: AZCOVIDTXT, a bilingual, two-way information sharing platform was created in April of 2020 in response to rising COVID-19 cases in Arizona. The aim of this paper is to delineate the protocol and processes used to develop and disseminate health messaging to serve as guidance for other groups, universities, or public health programs in the implementation or enhancement of health communication services. Methods: Health messaging formats included website articles, published on the system’s website (azcovidtxt.org), infographics posted on social media, and SMS. Social media and SMS infographics were intended to highlight and augment the topics covered in the weekly website articles, to create a seamless multimodal source of reliable COVID-19 information for AZCOVIDTXT enrollees and the broader public. All health messaging information, text message and social media content was planned and reviewed collaboratively by the AZCOVIDTXT team topic experts for accuracy, efficacy, and content consistency. Results: As of July 2021, AZCOVIDTXT provided weekly COVID-19-related health communication to 3,747 participating households located across 225 Arizona zip codes. AZCOVIDTXT has developed and sent 446 unique, bilingual SMS for a total of 271,977 contact points. The team has produced and published 179 website articles, which averaged a combined 7,000-page views per month, and 173 social media posts were made available to 268 followers across 3 platforms. Discussion: Several programmatic aspects were deemed essential to the success of AZCOVIDTXT. These included (1) addressing community specific needs, (2) creating timely and relevant content, (3) developing an adaptable system, and (4) prioritizing system automation where possible, (5) having an interdisciplinary team approach to identifying and crafting key messages.